Enhancing the construction innovation practices - AL SHAHER, BASSEL (2020)
This research aims to investigate the impact of planning on construction projects duration in Dubai. The primary data has been gathered through a questionnaire which was distributed among the project managers of different construction companies of Dubai (UAE) to investigate their opinions. The secondary data has been presented in the literature review which has been gathered from books, reports, and academic journals. The analysis of the correlation has been provided to understand the relationship among the independent and dependent variables of the research. The conclusion has been drawn at the end, and suitable recommendations have been provided for project managers of construction companies.